Factor Analysis of Student Learning Motivation Independent Learning Curriculum - Wibisono, Dhika Dzulkarnain; Eliasa, Eva Emania (Journal of Public Policy Analys, 2025)
This research investigates the multifaceted dimensions of student learning motivation within the context of independent learning curricula, employing factor analysis to dissect the underlying constructs and their inter-relationships. The study aims to provide a nuanced understanding of the key motivational factors that drive student engagement, persistence, and academic success in self-directed learning environments. This study employed a quantitative research design, utilizing survey methodology to collect data from a sample of students enrolled in independent learning programs. The survey instrument was designed to capture a comprehensive range of motivational variables, including intrinsic motivation, extrinsic motivation, goal orientation, self-efficacy, task value, and achievement motivation. Confirmatory factor analysis was then used to validate the factor structure and assess the model fit. Specifically, the independent learning curriculum focuses on enhancing the student's satisfaction in learning and promoting students' deep involvement in learning activities to enrich their experience and foster long-life learning. The result revealed that student learning motivation significantly impacts their satisfaction, involvement, competence, achievements, and overall performance. Furthermore, learning curricula place a greater emphasis on student autonomy, self-regulation, and personalized learning pathways, necessitating a deeper exploration of the motivational mechanisms that underpin effective learning outcome